Sosialisasi Pemanfaatan Tanaman Obat Keluarga (Toga) dalam Meningkatkan Daya Tahan Tubuh di Panti Asuhan Aisyiyah Kupang - Rr. Listyawati Nurina; Ika Febianti Buntoro; Conrad L. H. Folamauk; Muntasir Muntasir; Muhajirin Dean (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Covid-19 is a disease caused by the SARS-CoV-2 virus and attacks the human immune system. The most common signs and symptoms are fever, cough, shortness of breath, or dyspnea. One way that can be done by the community is by using materials from nature or medicinal plants. The utilization of Family Medicinal Plants (TOGA) has a positive impact on the immune system to prevent transmission of Covid-19. Community service activities are carried out through face-to-face outreach on Monday, 8 August 2022 at the Aisyiyah Orphanage, Kupang City. The application of using TOGA is expected to be able to support orphans in terms of health, especially during the Covid-19 pandemic in increasing/maintaining body immunity. Evaluation of the understanding of socialization participants is carried out by holding a short quiz at the beginning and end of the activity. The increased enthusiasm of participants in answering quizzes at the end of the activity showed an increase in knowledge regarding the use of family medicinal plants (TOGA) to increase endurance during the Covid-19 pandemic. Participants who successfully answered the quiz at the end of the activity were given a gift package as a form of appreciation for their seriousness in participating in this activity